Asistensi Mengajar di Yayasan Sulamuttarbiyah Barito Kuala - Amirul Azis Anshari Muda; Aulia Ahmad Fauzi Noor; Dina Selvia; Muhammad Andrean Lazuardi; Muhammad Choirul Hadi Santoso; Nana Fitriani; Siti Aisyah; Syah Warunadwipa Andiantosa (Borneo Research and Educatin Center, 2021)
The objectives of the program